A case report of maternal death due to dural arteriovenous fistula - Azin Niazi; Maryam Moradi; Maryam Salari Hadaki; Nafiseh Saghafi; Payam Sasannejad (Mashhad University of Medical Sciences, 2021)
Introduction: Dural arteriovenous fistula is a rare neurological disease. In this study, a case of maternal death due to dural arteriovenous fistula was reported.  Case presentation: The patient was a 19-year-old woman, G2 P2 who complained of memory impairment (forgetfulness) and headache 38 days after cesarean section and referred on outpatient basis, while she could not remember the names of her husband and child, and saw the lines but was not able to read. According to the results of the CT scan and the urgent need for intensive care, she was transferred to the ICU with the diagnosis of a neurologist. On the sixth day of hospitalization, the patient suffered from generalized tonic-clonic seizures and loss of consciousness. Initial drug therapy was performed and emergency CT scans were requested. Severe cerebral edema was reported on CT, which could be due to subarachnoid or pseudo-subarachnoid hemorrhage. CT angiography, MRI and MRV revealed a dural arteriovenous fistula. The patient underwent surgery the same day. Three days after the surgery, the patient suffered a cardiac arrest, which was immediately followed by CPR, cardiac massage, and medication, which unfortunately was not successful after 45 minutes of CPR, and the patient died. Conclusion: Women who suffer from postpartum headaches should be evaluated accurately and quickly. In addition, the occurrence of seizures in pregnant women and the initial diagnosis of eclampsia should not prevent the physician from paying attention to other important and deadly differential diagnoses.